2012
DOI: 10.1111/j.1752-4598.2011.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Current protected sites do not allow the representation of endangered invertebrates: the Spanish case

Abstract: 1. Using a recently created database representing the joint effort of around 100 invertebrate taxonomists, this study uses the information on 52 arthropoda and 27 mollusca species that are endangered and critically endangered to examine to what extent invertebrate species are represented in existing Spanish protected areas.2. As distribution information is available at a 100 km 2 resolution, we consider different area thresholds to judge cells as being protected.3. Approximately 19% of the area represented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
4
15
0
1
Order By: Relevance
“…Our results confirm that current Spanish protected areas and even the Nature 2000 network do not adequately represent threatened terrestrial invertebrates (Verdú et al 2011, Hernández-Manrique et al 2012. Although most of these species inhabit in hot spot cells, which present a comparative significantly lower proportion of anthropised area and a higher percentage of protected area, only 35 % of these cells have more than 2 % of their area currently protected, and more than half of these hot spot cells would have \15% of their area protected.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm that current Spanish protected areas and even the Nature 2000 network do not adequately represent threatened terrestrial invertebrates (Verdú et al 2011, Hernández-Manrique et al 2012. Although most of these species inhabit in hot spot cells, which present a comparative significantly lower proportion of anthropised area and a higher percentage of protected area, only 35 % of these cells have more than 2 % of their area currently protected, and more than half of these hot spot cells would have \15% of their area protected.…”
Section: Discussionsupporting
confidence: 92%
“…Undesignated sites are also important since red‐data‐book species richness is maximal on these sites and this may be related to the need for disturbed habitats such as basking areas, particularly for C. clatratus . A comprehensive analysis of red‐data‐book species in Spain showed that most species’ ranges occurred outside designated areas (Hernámdez‐Manrique et al ., ) and so, in general, there may be a need to either alter the management within designated areas or integrate areas outside the conservation network by improving upon current agri‐environmental schemes via the inclusion of considerations of invertebrate ecology. A ‘mesofilter’ approach within‐sites by the conservation of ‘critical ecosystem elements’ (Hunter, ), such as areas of disturbance that may act as basking areas or improved feeding areas for predatory species and adopting a general ‘synthetic management approach’ at the landscape scale (Samways, ) by applying consistent management regimes within sites, but contrasting regimes among sites, would aid this task.…”
Section: Conclusion and Implications For Conservation Policy And Prasupporting
confidence: 68%
“…Despite the large extent of the Iberian conservation area networks, many species are still not covered by these areas. This is especially true for non-charismatic species groups like lichens or invertebrates which are usually underrepresented (e.g., Martínez et al 2006;Araújo et al 2007;Hernández-Manrique et al 2012).…”
Section: Introductionmentioning
confidence: 99%